1990
DOI: 10.1111/j.2042-7158.1990.tb05374.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Some Preservatives Used in Nasal Preparations on the Mucus and Ciliary Components of Mucociliary Clearance

Abstract: Efficient mucociliary clearance is a function of the physical properties of the mucus coupled to appropriately functioning cilia and may be altered by substances affecting ciliary beat frequency (CBF). Therefore the effect of preservatives on CBF was investigated using a photoelectronic technique. Methyl-p-hydroxybenzoate, propyl-p-hydroxybenzoate, chlorbutol and chlorocresol inhibited beat frequency, an effect which was reversible upon rinsing out the first three compounds but not chlorocresol. The effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Frog palates can be obtained in large quantities, the frog palate is a robust tissue giving reproducible results, and the experimental technique is well established, with many transport studies having been performed with this model. [24][25][26][27][28][29] In contrast, human turbinates are in limited supply and the tissue is more fragile and sensitive to sub-optimal conditions than the frog palate. However, this human model also gives reproducible results, which alludes to the possibility of identifying subtle differences between the effects of various compounds on MTR.…”
Section: Discussionmentioning
confidence: 99%
“…Frog palates can be obtained in large quantities, the frog palate is a robust tissue giving reproducible results, and the experimental technique is well established, with many transport studies having been performed with this model. [24][25][26][27][28][29] In contrast, human turbinates are in limited supply and the tissue is more fragile and sensitive to sub-optimal conditions than the frog palate. However, this human model also gives reproducible results, which alludes to the possibility of identifying subtle differences between the effects of various compounds on MTR.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas chlorocresol, edetate, benzalkonium chloride, phenylmercuric acetate and thiomersal caused irreversible damage. Phenylmercuric acetate and thiomersal were shown to be more ciliostatic than benzalkonium chloride [ 93 , 122 , 123 ]. However, a study published by Rijntjes et al focusing on the long-term administration of 0.02% benzalkonium chloride as preservative proved the safety of the drug supplement as it did not cause changes in nasal mucosal morphology or effects on mucociliary clearance [ 93 , 124 ].…”
Section: Formulations Dosage Forms and Medical Devices For Intranmentioning
confidence: 99%
“…The interest in rhinitis medicamentosus caused by mucus constrictors and preservatives included in nasal drops has been reported since the 1980s. In 1989, Batts et al 9 reported that BZC exhibited a toxic effect on palatal ciliary movement in frogs. In 1995, Braat et al 10 revealed that 0.02% BZC did not have significant effects on cilia of patients with seasonal allergic rhinitis.…”
Section: Discussionmentioning
confidence: 99%